A1.86 The influence of TNFα on the expression of genes of the molecular clock in the synovial tissue. (31st January 2014) - Becker, TM; Humpeler, S; Baarsen, Lvan; Gerlag, D; Tohidast-Akrad, M; Zenz, P; Kiener, HP; Ekmekcioglu, C; Steiner, G
Abstract : Background: Patients with rheumatoid arthritis (RA) show modulated circadian rhythms of inflammatory cytokines and cortisol suggesting potential involvement of clock genes (CG) in the pathophysiology of RA. In our study we aimed to examine the expression and localization of clock genes in synovial tissues of patients with RA compared to the expression in samples of patients with osteoarthritis (OA). Additionally we investigated the expression of certain clock genes in the synovial tissue of RA or psoriatic arthritis (PsA) patients before and after administration of common TNF inhibitors. Methods: Synovial fibroblasts (SFs) of patients with RA or OA were synchronised by serum shock or treated with TNFα and gene expression profiles of different CG were determined over 24 hours by real time PCR. The expression of CG in RA and PsA patients was determined before and after administration of TNF inhibitors by real time PCR. Additionally, the in situ expression of clock genes in synovial tissues was examined by immunohistochemistry. Results: Immunohistochemical analysis revealed that CG are expressed in B-cells, macrophages and fibroblasts but not in T-cells of the synovial tissue but the percentage share of expressing cells is comparable between RA and OA patients. Furthermore we could show that cultured human SFs can be synchronised by TNF a and that this synchronization differs from the synchronization under standard conditions (serum shock). The inflammatory condition with TNFa leads to phase shifts in the expression profiles of some CG and therefore differences in the expressional intensity at different time points. However, the application of TNF blockers such as infliximab in RA patients or adalumimab in PsA patients had no effect on the expression patterns of CG in synovial tissue. Remarkably, a dramatic downregulation of most CG was observed 48 hrs after start of therapy, both in the inflimiximab and the placebo group which might be caused by the first biopsy (i.e. mechanical stress) performed immediately before start of therapy or, alternatively, be related to the fact that participation in the study may create a stressful situation for the hospitalised patient. This phenomenon would certainly deserve further investigation. Conclusion: Although TNFα can modulate CG expression in vitro, expression of CG does not appear to be altered in synovial tissue of RA patients and CG expression is not affected by anti-TNF therapy.